2012
DOI: 10.1039/c1dt11176k
|View full text |Cite
|
Sign up to set email alerts
|

One-step synthesis of cubic FeS2and flower-like FeSe2particles by a solvothermal reduction process

Abstract: In this paper, for the first time a simple batch process was utilized for the facile synthesis of cubic FeS(2) and flower-like FeSe(2). By adjusting the amount of solvents and surfactants added, pure pyrite FeS(2) with a defined crystalline structure was obtained. It was found that the reaction temperatures and iron sources had significant influence on the purities and morphologies of FeS(2) and FeSe(2) particles. Raman spectra of the FeS(2) and FeSe(2) samples presented characteristic peaks of S-S and Se-Se a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(104 citation statements)
references
References 31 publications
(20 reference statements)
3
97
0
Order By: Relevance
“…At higher temperatures, the system has enough thermal energy to increase the growth rate and form lamellate structures. [13] Additionally, Figure 4(d-f) shows SEM images of samples grown for different times. The XRD analysis reveals that these samples consist of orthorhombic FeSe 2 mixed with residual Se.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…At higher temperatures, the system has enough thermal energy to increase the growth rate and form lamellate structures. [13] Additionally, Figure 4(d-f) shows SEM images of samples grown for different times. The XRD analysis reveals that these samples consist of orthorhombic FeSe 2 mixed with residual Se.…”
Section: Resultsmentioning
confidence: 97%
“…[10][11][12] New methods to achieve the facile synthesis of threedimensional FeSe 2 micro/nanostructures with improved performance are thus highly needed, and several attempts in this direction have been reported. Flower-like FeSe 2 particles has been reported by Luan et al, [13] whereas Son and coworkers developed an organometallic approach to synthesize the FeSe 2 nanostructures. [14] However, developing a facile method to obtain pure FeSe 2 materials with specific morphologies still represents a significant challenge.…”
Section: Introductionmentioning
confidence: 97%
“…In the past decade, types II-VI and IV-VI semiconductor nanocrystals (so-called quantum dots, abbreviated as QDs) such as CdSe, CdTe, and PbSe and their alloys have been intensively studied due to their appealing optical properties such as narrow emission bands, emission wavelength tunability with size, and photostability [1]. They have promising applications in solar cells [2][3][4], heat electrical application [5], light-emitting diodes (LED) [6,7], sensors [8], fluorescent probes [9,10], biolabeling [11], anticounterfeiting [12], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the absorbance of these final cubes mocked those of irregular shape. Most cubic pyrite nanostructures in the literature show absorbance in the NIR [24,44]. This could show that size indeed affects the absorbance of these particles or that some other phenomenon is occurring such as plasmonics.…”
Section: Precipitation Methodsmentioning
confidence: 95%
“…Yuan et al showed by utilizing Hematite (Fe 2 O 3 ) and elemental sulfur as the chalcogenide along with oleic acid (OA), oleylamine (OLA) and CTAB, cubic structures could be obtained [44]. All components are loaded into one flask and heated up to 290°C and kept there for 1 h with stirring.…”
Section: Precipitation Methodsmentioning
confidence: 99%